Nghiên cứu tính hấp thụ sóng điện từ của vật liệu nanocompozit trên cơ sở nhựa epoxy và cacbon nanotube - Sơn, Hoàng Anh; Nam, Phạm Hồng; Minh, Phan Ngọc (Vietnam Journal of Chemistry, 2014)
The electromagnetic interference shielding features were characterized by three behaviors such as reflection, transmission and absorption. The electromagnetic interference shielding efficiency of nanocomposite materials based on carbon nanotube (CNTs) containing epoxy resins has been investigated using vector network analyzator HP 8270D. Studying the influence of CNTs concentration and the material thickness on the electromagnetic absorption properties at X band (8 - 12 GHz) showed that a sample with CNTs concentration 5% and thickness 1 cm electromagnetic absorbance attains average more than 0.9.